www.rnaworkbench.com: A new program for analyzing RNA interference - Vareková, Radka Svobodová; Bradác, Ivan; Plchút, Martin; Skrdla, Michal; Wacenovsky, Michael; Mahr, Helmuth; Mayer, Georg; Tanner, Herbert; Brugger, Hermann; Withalm, Josef; Lederer, Peter; Huber, Heinrich; et al. (Computer methods and programs in biomedicine, 2008)
RNA interference (RNAi) has become an important tool to study and utilize gene silencing by introducing short interfering RNA (siRNA). In order to predict the most efficient siRNAs, a new software tool, RNA Workbench (RNAWB), has been designed and is freely available (after registration) on http://www.rnaworkbench.com. In addition to the standard selection rules, RNAWB includes the possibility of statistical analyses of the applied selection rules (criteria). The role of RNA secondary structures in the RNA interference process as well as the application of sequence rules are discussed to show the applicability of the software.
Keywords: algoritmy; RNA Interference; Gene Targeting; RNA, Small Interfering; sekvenční analýza RNA; software; Base Sequence; Software; Molecular Sequence Data; molekulární sekvence - údaje; RNA interference; malá interferující RNA; genový targeting; Sequence Alignment; sekvenční seřazení; Sequence Analysis, RNA; sekvence nukleotidů; Algorithms